Pengaruh PENGARUH LITERASI KEUANGAN, FITUR LAYANAN, DAN KEMUDAHAN PENGGUNAAN TERHADAP PENGGUNAAN E-MONEY - Susanti, Aulia Puspa Giriani; Susanti, Susanti (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2021)
The research was conducted to determine and analyze the effect of financial literacy, service features, and ease of use on the use of e-money. This type of research is a quantitative research. The technique used to obtain the research sample was random sampling technique, amounting to 110 active student respondents in the Accounting Education Study Program, State University of Surabaya. The data analysis method used is multiple linear regression analysis, previously carried out by instrument tests and classical assumption tests. Followed by hypothesis testing using SPPS 25 software. The results of this study state that financial literacy has a negative and insignificant effect on the use of e-money, while partially service features and ease of use have a positive and significant effect on the use of e-money. Meanwhile, simultaneously states that financial literacy, service features, and ease of use have a significant influence on the use of e-money.